SOCIAL ACTOR REPRESENTATION OF INDONESIAN MIGRANT WORKERS’ EXECUTIONS IN SAUDI ARABIA - Utama, Gina Nanda; Amalia, Rosaria Mita; Yuliawati, Susi (Sanata Dharma University, 2020)
This study aims to describe how the Middle East Media represent the Indonesian government and the executed Indonesian migrant workers in the case of Indonesian migrant workers’ executions in Saudi Arabia. The data are analyzed through Critical Discourse Analysis focuses on the representation of social actors by Van Leeuwen (2008). This theory examines how the social actors are presented or excluded in the representation. In addition, the analysis of this study is also supported by the lexical analysis based on Richardson’s theory (2007) of analyzing news text: level of analysis. This study uses descriptive analysis method since the data are analyzed based on the indicators, categories or strategies in the theories which are used to analyze the data. This study found that the Indonesian government is represented as the party who has done many efforts to save Indonesian migrant workers from the executions abroad but on the other side, Indonesian government is also represented as hypocritical party since Middle East Media nominate the Indonesian government as the party that still implement the death penalty. Generally, the lexical analysis show that the executed Indonesian migrant workers are represented as the cruel killers although several media present another information which show their reasons to do the crimes such as self-defense and suffering mental-illness.